Diferensiasi Tanda Waqaf Mushaf Standar Indonesia 2008 Dan Mushaf Madinah 1439 H - Lilik Ummi Kaltsum Lilik; Mulqi Yagiasa Ulfah (Institut Agama Islam Negeri (IAIN) Keiri, 2022)
This study examined the difference between the waqf marks of the Indonesian Standard Mushaf and the Medinan Mushaf. The distinction between the two manuscripts lies in their marking and placement. It focused on the factors causing the differences and determining whether or not the effect of differences on meaning. The method used was the comparative analysis method by analyzing and comparing the two manuscripts. The object under study is QS. al-Baqarah in the 2008 Indonesian Standard Mushaf and the Medina Mushaf published by Mujammā al-Mālik Fāhd 1439 H, and corroborated by the results of interviews. The findings from this tracking were: 1) There are similarities and differences in the placement of waqf marks in the Indonesian Standard Mushaf and the Medinan Mushaf in QS. al-Baqarah. 2) The similarities in the placement of waqf signs are 143 and the difference is 456. 3) The factors that caused differences between the placement of waqaf signs in the Indonesian Standard Mushaf and the Medina Mushaf are different from understanding the editorial composition of the Qur'an in terms of Balaghah science in its three branches, namely 'Ilm al-Bayān, 'Ilm al-Ma'ānī, and 'Ilm al-Bādī’.